A Review of Work-Life Balance Practices Prevalent in Public Sector Undertakings in India - Anuradha; Pandey, Mrinalini (Prabandhan: Indian Journal of Management, 2015)
Work-life balance has become an important issue in the twenty first century. Work and family life are two sides of the same coin as both are interconnected and interfere with each other. Increased work demands interfere with family life, and on the other hand, family demands interfere with the work-life of employees. Therefore, conflicts occur, which negatively affect an employee's performance at work as well as at home. Looking at the trend, organizations have increasingly started to take an active interest in implementing practices that enable employees to cope with the work-life balance issues. The study attempted to explore the work-life balance practices of selected public sector undertakings and their impact on organizational performance. The finding suggested that public sector organizations in India have realized that work-life balance practices are crucial for organizational performance.